DISRUPTIVE IMPACTS AND PARADIGM SHIFT IN UNDERGRADUATE PHYSICAL EDUCATION: THE CASE OF A STATE UNIVERSITY - Alvin John M. Carlos; Nomer Varua; Ariel F. Banting; John Kerby Amononce; Melvin N. Escartin (Universitas Bina Mandiri Gorontalo, 2025)
The unexpected surge of the COVI19 pandemic in the early part of 2020 has greatly impacted the way things are done in many aspects of life, including higher education. The impact has affected both higher education institutions (HEIs) in developed and developing countries at varying levels. With the goal of providing continuous education, HEIs have responded to the call of the time, implementing a relatively abrupt transition to distance online learning, exposing the many challenges of delivering higher education courses, particularly skills-based collegiate courses such as Physical Education (PE). In the Philippines, where there is still a great digital divide and access to learning technologies are still limited when the pandemic hit, the delivery of physical education has been disrupted and teachers of PE must shift their paradigm of teaching and learning. This reflective research, utilizing both quantitative and qualitative research designs, aims to describe the effects of COVID19 on physical education in a public higher education institution in a developing country. Face-to-face teaching and learning have been shifted to remote distance/virtual learning and on-site demonstrations of PE skills were suspended for almost two academic years now. Affected by various social, financial, infrastructure, and political factors, PE in the Philippines has been greatly disrupted and a paradigm shift has been the answer to adjust and recalibrate the delivery of education. Internet accessibility, affordability, reliability, and availability of resources in certain areas seem to negatively impact the delivery of PE during the long lockdowns. Appropriate mitigation mechanisms based on the results are recommended to help in responding, mitigating, and recovering quickly from future pandemic occurrences.